Potency of Gastropods as Ecological Bioindicators in the Anthropogenic Waters of Geger Beach Bay, Bali - Farhan Yudhistira Kurniawan; Maria Inggrit Indrayanti Soko; Uni Putri Audia Marpaung; I Made Dwi Guna Wijaya; Made Dendy Pratama (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The increasing pressure of tourism and urbanization in coastal areas like Bali often leads to environmental degradation, necessitating a robust biomonitoring system. Gastropods serve as ideal ecological bioindicators due to their limited mobility and specific tolerance to environmental stress. This study aims to assess the water quality of Geger Beach Bay using gastropods as indicators. Observations were conducted at three stations—upstream, midstream, and downstream—using the quadrant transect method. Community analysis included diversity (H'), evenness (E), and dominance (C) indices, alongside physicochemical water parameters. The results showed significant variations in community structure. The downstream station recorded the highest diversity (H' = 2.47) and abundance (129 individuals) due to stable salinity, while the upstream station had the lowest diversity (H' = 1.31) despite high DO, likely due to unstable substrate. PCA analysis confirmed that DO, temperature, and salinity were the primary environmental drivers. Low salinity (15-17 ppt) and pH levels indicate freshwater dilution from nearby hotel effluent. Overall, gastropods are effective bioindicators for coastal health, providing a scientific basis for sustainable management, specifically recommending improved wastewater treatment to preserve biodiversity.